Hinduism and modernity - Smith, David (Blackwell Pub., 2003)
This innovative book offers a dynamic analysis of Hinduism in the perspective of Western notions of modernity. After reviewing definitions of modernity and Hinduism and looking at modernity in India, the author considers Hinduism in relation to Islam and the West. The second half of the book presents key aspects of Hinduism, ancient and modern, in the light of their contrast with modernity. The scope of the book is extremely broad, covering topics such as Orientalism, women, goddesses, gods, and the central problem of contemporary Hinduism - the rise of Hindu nationalism. The book will be of interest not only to students of Hinduism but also to all those interested in the sociology of religion more broadly, and indeed everyone interested in the conjunction of modernity and tradition.